Recent Publications upon Economics (Quarterly Journal of Economics, 1887)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 507–512, https://doi.org/10.1093/qje/1.4.507 Published: 01 July 1887